2021
DOI: 10.3390/nu13061841
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Relationship between Sugar Content, Packaging Features, and Food Claims of Breakfast Cereals

Abstract: Excessive free-sugar intake has become highly prevalent in numerous countries, and Portugal is not the exception. One product category that contributes to the daily intake of free sugars is breakfast cereals. In the current work, we identified 289 exemplars from two major retailers in Portugal and collected information on their nutritional profile (e.g., sugar, salt, fiber per 100 g), price, packaging features, type of food claims present (e.g., statements about the composition, sensory features, the origin of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 46 publications
0
9
0
Order By: Relevance
“…Once again, the "cereal" category, with more than 40% of the products carrying a NC, was the most representative category for number of NC [20]. A recent paper of Prada et al concerning 289 breakfast cereals sold in Portugal highlighted similar results, with an average of 3.9 total claims per product, 70% of which related to the nutrient composition (no data on fibre-related claim) [18]. Similarly, Davidovic et al [24] recently observed that 81.3% of breakfast cereals sold on the Serbian market displayed at least one NC.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Once again, the "cereal" category, with more than 40% of the products carrying a NC, was the most representative category for number of NC [20]. A recent paper of Prada et al concerning 289 breakfast cereals sold in Portugal highlighted similar results, with an average of 3.9 total claims per product, 70% of which related to the nutrient composition (no data on fibre-related claim) [18]. Similarly, Davidovic et al [24] recently observed that 81.3% of breakfast cereals sold on the Serbian market displayed at least one NC.…”
Section: Discussionmentioning
confidence: 85%
“…Based on these considerations, the aims of the present study were to: (1) evaluate the nutritional composition of breakfast cereals currently sold in Italy by retrieving information from the food packaging and (2) investigate differences in terms of energy, macronutrients and salt contents among products with and without fibre-related NCs. These products were chosen since they bear a high number of NCs [ 18 ]. This work was conceived within the Food Labelling of Italian Products (FLIP) study which systematically investigates the nutritional quality of food products currently sold in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, breakfast cereals exhibit greater diversity (Angelino et al., 2023; Devi et al., 2014), encompassing various key constituents, including sugar, saturated fats, fiber, and protein, contributing to the final grade. Although reformulating breakfast cereals by increasing fiber or protein may enhance their nutritional profile and NS grade, it does not address the core issue of excessive added sugar (Prada et al., 2021). We must mention that, similarly to whole grains, added sugar is also not part of mandatory food labeling (European Commission, 2011); therefore, it would be very challenging to include it into NP.…”
Section: Discussionmentioning
confidence: 99%
“…These data reaffirm the interest of consumers in more natural and healthy products. Previous studies, Lähteenmäki (2013) and Prada et al (2021) indicate that consumers have been opting for alternatives with low concentrations of added sugar since this ingredient is related to some chronic diseases. For the format, 66% (77) of consumers indicated that they prefer the cereal in a ball shape, and 35% (41) indicated that the commercial format as corn flakes would be an interesting alternative since the product would be crispier.…”
Section: Market Researchmentioning
confidence: 99%